How do analysts interpret management range forecasts?. (April 2015) - Tang, Michael; Zarowin, Paul; Zhang, Li
Abstract: Range forecasts have evolved to be the most common form of management forecasts. Prior studies typically use the midpoint to evaluate analyst reaction to range forecasts, implicitly assuming that analysts place equal weights on the upper and the lower bounds of management range forecasts. We empirically test this restrictive assumption and provide strong evidence of unequal weights – analysts place significantly more (less) weight on the lower (upper) bound of forecast ranges. Moreover, such overweight on the lower bound is more pronounced when analysts face higher ambiguity, consistent with the "max–min" axiom, which predicts that decision-makers tend to assign higher probability to the worst-case scenario when facing ambiguity. Further tests show that "optimal revisions" with perfect foresight of actual earnings also overweight the lower bound.